A Comparison of Preferred Urban Administrative Dispositions Between Constituency Groups. (September 2015) - Pregot, Michael
This research study analyzes preferred leadership dispositions for teachers, parents, and school leaders. Respondents selected their most preferred dispositions from a list of 20 (Interstate School Leaders Licensure Consortium) leadership standards. Similarities and differences were discerned among the constituent groups. School leaders, teachers, and parents were strongly correlated in their aggregate ranked preferences yet data evidenced unique differences expressed by each group. As a result of the findings, there are inferences suggested for school leaders to consider in their leadership role.